Influencing Factors for Sleep Quality Among Shift-working Nurses: A Cross-Sectional Study in China Using 3-factor Pittsburgh Sleep Quality Index - Li Zhang, BSc; Dong-mei Sun, MD; Chang-bing Li, BSc; Min-fang Tao, MD (Elsevier, 2016)
Purpose: The aim of this study was to identify influencing factors for sleep quality among shift-working nurses based on a three-factor scoring model that included sleep efficacy, sleep quality and daily dysfunction. Methods: A cross-sectional survey of 513 nurses in a hospital in Shanghai, China, was conducted using a self-reported questionnaire. Sleep quality was measured by the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed based on the three-factor PSQI model: Factor 1, sleep efficacy; Factor 2, sleep quality; Factor 3, daily disturbances. Results: After adjusting for age, marital status, and having children, multivariate logistic regression analysis showed that participants who had previous shift work experience which was at least 6 months ago, or were currently performing shift work were significantly more likely to have poor sleep quality (PSQI > 5) than those who had never done shift work (adjusted odds ratios of 3.943 and 3.975, respectively, both p < .001). Mean scores of the three individual factors increased significantly among nurses currently performing shift work compared with those who had never done shift work (Factor 1, β = 0.61, p < .001; Factor 2, β = 1.86, p < .001; Factor 3, β = 0.45, p = .002). Mean scores of Factor 2 and Factor 3 increased significantly among nurses with previous shift work experience compared with those who had never done shift work (Factor 2, β = 1.15, p = .003; Factor 3, β = 0.52, p = .005). Conclusions: Performing current shift work and performing shift work previously were significantly associated with poor sleep quality. An appropriate arrangement and intervention strategies are needed in Chinese hospitals in order to improve sleep quality among shift-working nurses.